An Empirical Study on Environmental Laws Awareness Among College Students of Kashmir Valley - Bilal Ahmad Bhat; Nazia Fayaz Azad; Iqra Firdous; Sidrat Ul-Muntaha Anees; Samira Khan; Zeenat Islam; Uzma Nazir; Qazi Nusrat; Arshi Rafiq; Mohammad Inam Bhat; Intizar Ahmad (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
India, with its wealthy biodiversity and numerous ecosystems, has lengthily diagnosed the significance of environmental conservation for sustainable development. Environmental regulation in India encompasses a vast variety of criminal principles, regulations, and insurance policies that goal to defend and retain the environment, stop pollution, and promote sustainable use of herbal resources. In this study, we use a well-designed validated questionnaire to collect the information from 400 College students (200 male and 200 female) via online/offline mode using simple random sampling. The data collected was analysed statistically using statistical software SPSS (Version 20). The results of our study revealed that majority of respondents were not aware of legal laws, an important part of healthy society. It is important for every individual to study and know about environmental laws as it helps in understanding the environmental principles and regulations that govern the protection of environment. Statistically, non-significant difference was observed between Arts and Science Stream students in practice towards environment (P>0.05). Finally, it was suggested that legal literacy about environmental laws may be promoted as it will make society more fair and useful to protect the environment and address global issues related environment.